Severe ovarian hyperstimulation syndrome requiring recurrent large-volume paracenteses until 21 weeks' gestation: a case report - Chelsea A. Henshaw, M.D; Gregory W. Kirschen, M.D., Ph.D; Lucy Chen, M.D; Arthur J. Vaught, M.D; Katie Cameron, M.D; Mindy Christianson, M.D (Elsevier, 2022)
Objective: To report a case of severe ovarian hyperstimulation syndrome (OHSS) persisting into the late second trimester of a singleton pregnancy. Design: Case report. Setting: Academic tertiary care center. Patient(s): A 29-year-old woman with severe OHSS after fresh embryo transfer after controlled ovarian hyperstimulation requiring intervention until 21 weeks' gestation in a singleton pregnancy. Intervention(s): Thorough evaluation of an unusual case of severe OHSS and medical/procedural management of its sequelae in the setting of ongoing pregnancy. Main Outcome Measures(s): The clinical development of severe OHSS during pregnancy and its effect on pregnancy outcomes. Result(s): Severe OHSS persisted until 21 weeks' gestation with reaccumulating ascitic fluid, which impacted pregnancy outcomes. Conclusion(s): Clinicians should be aware of the risk of severe OHSS and its possible effect on pregnancy outcomes beyond the first trimester.